Dinamika Kepribadian Narapidana Kasus Pembunuhan dengan Gangguan Kepribadian Antisosial - Nanda Audia Vrisaba; Ktut Dianovinina (Journal An-Nafs: Kajian Penelitian Psikologi, 2019)
Antosocial personality disorder experienced by someone caused them to take deviant actions and violate the norms and values of their surrounding, so that many of them are prisoners who are in custody. This study aims to determine the personality dynamics possessed by prisoner who experienced antisocial personality disorders. The researcher will also identify several causes that make up a person experiencing an antisocial personality disorder. The researcher used a case study method with a qualitative approach. There is one participant in this study, namely Mahmud, an prisoner of a homicide and involved in an abductions case. During the research process, researcher used observation, interviews, and several psychological tests. The finding shows that antisocial personality disorders experienced by participants was not formed when he was in the adult period, but since his childhood some deviant behavior were indicated. In addition, external factors also have influence in forming a person who has an antisocial personality disorder.